PENGARUH KEPEMIMPINAN, KETERAMPILAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA HOME INDUSTRI GULA MERAH DI KECAMATAN PEGAJAHAN KABUPATEN SERDANG BEDAGAI - Ramadhan Cik, Muhammad Rizky; Rukmini; Hidayat, Toni; Siregar, Horia (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2024)
This research sought to ascertain how employee performance in the Brown Sugar Home Industry in Pegajahan District, Serdang Bedagai Regency, was impacted by work environment, skills, and leadership. In this quantitative investigation, seventy individuals were sampled. For data processing, SPSS 25.0 was used. Multiple linear regression, using the equation Y = 2.116 + 0.597X1 + 0.461X2 + 0.143X3, was the data processing technique used. The partial T test findings indicated that the significance 0.000 <0.05 and Tcount 8.487 > Ttable 1668. These findings show that Ha is accepted and H0 is rejected, proving that leadership significantly and favourably affects worker performance. The Tcount value of 4.630> Ttable1668 and significant 0.000 <0.05 indicated that skills had a positive and significant influence on employee performance, supporting the adoption of Ha and rejecting H0. The results of Tcount value of 1.878> Ttable1668 and significant 0.044<0.05 show that the work environment has a positive and significant impact on employee performance, indicating that Ha is accepted and H0 is rejected. It can be concluded that Ha is accepted and H0 is rejected based on the results of the simultaneous F test, which show an Fcount value of 65.853> Ftable 2.74 and significant 0.000<0.05. This suggests that skills, leadership, and the work environment all have a positive and significant impact on employee performance.